En undersøgelse af mundtlighed på Københavns Universitets bacheloruddannelse i Dansk - Hjuler, Sine; Larsen, Anna Kragskov (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2017)
In this article, we investigate how oral proficiency teaching is represented in the Bachelor of Arts in Danish at the University of Copenhagen. Our target groups are students at their third semester who are following the curriculum of 2012, and their teachers. We find that the curriculum of 2012 has a variety of broad formulations concerning requirements of written and spoken language, respectively. Even though the students consider themselves competent in spoken language, they express a wish for more education in this field. We find that oral proficiency teaching at the Bachelor of Arts in Danish is not regarded as significant content at the University of Copenhagen, and that the limited focus on oral proficiency might be a result of non-existing norms of spoken language.